An energy-dense and thermal-stable bis-azobenzene/hybrid templated assembly for solar thermal fuel. Issue 21 (13th April 2016) - Feng, Wei; Li, Shipei; Li, Man; Qin, Chengqun; Feng, Yiyu
Abstract : A bis-azobenzene/hybrid assembly combining high energy density, high power density and tunable heat release was presented. Abstract : Designing an energy-dense and thermal-stable photo-isomerizable chromophore/hybrid template is a challenge for devising a highly customizable solar-heat conversion and storage technology. This study presents the templated assembly of close-packed 2-chloro-4, 6-bis(4-(phenyldiazenyl)phenoxy)-1, 3, 5-triazine (bis-azobenzene chromophores) covalently bound to reduced graphene oxide (RGO-bis-Azo). The steric configuration and energy of bis-Azo ( trans - and cis -isomers), calculated by density functional theory, are influenced by intra- and inter-molecular steric hindrance due to high grafting density and the bundling effect. This results in a dramatic increase in enthalpy and activation energy of the isomerization. The RGO-bis-Azo hybrid combines a high energy density of 80 W h kg −1, the maximum power density of 2230 W kg −1 and a tunable heat release time from 2 min to 5520 h. These findings pave the way for developing a chromophore/hybrid template for solar thermal fuel by optimizing molecular interaction.